METODE ZIG-ZAG DALAM MENINGKATKAN LATIHAN TEKNIK DASAR DRIBLING PADA PERMAINAN SEPAK BOLA SISWA KELAS V DI SD NEGERI 4 KECAPI KABUPATEN JEPARA - Hilmy Aliriad; Ainu Zuhriyah; Imam Nor Rif’an (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2016)
Dribbling is one of the basic techniques that has quite an important role in the game of football, it is not surprising if football observers specifically state that the skill of a player can be seen in how a player dribbles the ball. The problem in this study is